La captation des ressources en eau douce : la notion de dette à la lumière des marchés d’eau internationaux - Jochen Sohnle (VertigO)
What are the consequences of water diversion in international law? Are debts created? Can the abstracted water be placed on a market? In order to answer these questions, we must analyse first a number of key notions, such as fresh water resources, creditor, debtor, offerer and demander. Two main situations are then considered. The idea of water markets must be rejected when water is diverted within an international water basin or a transboundary aquifer. However, the idea of a water market is already a fact when the water diverted in accordance with the law is transferred outside the catchment area, through pipelines or through artificial or biological containers (virtual water).